State-of-the-art review of athletic wearable technology: What 113 strength and conditioning coaches and athletic trainers from the USA said about technology in sports. Issue 1 (February 2020) - Luczak, Tony; Burch, Reuben; Lewis, Edwin; Chander, Harish; Ball, John
Wearables are a multi-billion-dollar business with more growth expected. Wearable technology is fully entrenched at multiple levels of athletic competition, especially at the National Collegiate Athletic Association (NCAA) and professional levels where these solutions are used to gain competitive advantages by assessing health and performance of elite athletes. However, through the National Science Foundation (NSF) Innovation Corps (I-Corps) training experience, a different story emerged based on pilot interviews from coaches and trainers regarding the lack of trust in wearables, and how the technology falls short of measuring what practitioners need. An NSF I-Corps project was funded to interview over 100 strength and conditioning coaches (S&CCs) and athletic trainers (ATs) regarding the current state of wearables at the NCAA and professional levels. Through 113 unstructured interviews, a conceptual map of relationships amongst themes and sub-themes regarding wearable technology emerged through the grouping of responses into meaning units (MUs). Interview findings revealed that discussions by S&CCs and ATs regarding wearables could be grouped into themes tied to (a) the organizational environment, (b) the athlete, and (c) the analyst or data scientist. Through this project, key findings and lessons learned were aggregated into sub-themes including: the sports ecosystem and organizational structure, brand development, recruiting, compliance and gamification of athletes, baselining movement and injury mitigation, internal and external loads, "return tos, " and quantifying performance. These findings can be used by practitioners to understand general technology practices and where to close the gap between what is available versus what is needed.